Constructing interconnected graphene network in fluoroelastomer composites by F-H polar interaction for enhanced mechanical and barrier properties. (18th August 2017) - Wu, Yun-hui; Lin, Yong; Wei, Yong; Chen, Song; Liu, Shu-qi; Liu, Lan
Abstract: Graphene is one of the most promising fillers for functional nanocomposites due to its high strength, high conductivity and high specific surface area, etc. However, its poor interfacial compatibility makes it difficult to simultaneously satisfy high strength and low gas permeability of nanocomposites. Herein, we proposed a novel strategy to regulate interfacial adhesion by fluorine-hydrogen (F-H) polar interaction in the FKM composites. The F-H polar interactions effectively induce the graphene oxide (GO) interact with the chain of fluoroelastomer (FKM) in spatial arrangements on molecular-level, promoting the construction of interconnected GO network. Specifically, a 10-fold increase in tensile strength of FKM/GO-5 with the incorporation of 5 phr GO is realized compared with pure FKM, and the oxygen permeability of FKM/GO-5 decreases by 79%. At the same filler contents, FKM/GO-5 composites exhibit higher mechanical property and lower gas permeability compared with FKM/rGO composites. Such enhanced performances make FKM/GO composites with an interconnected network very competitive for potential applications as multi-functional structural materials. The proposed strategy provides a novel effective approach for developing and designing the high-performances fluorine-based polymer nanocomposites.